2020
DOI: 10.1111/jfbc.13336
|View full text |Cite
|
Sign up to set email alerts
|

HPLC determination of massoia lactone in fermented Cordyceps sinensis mycelium Cs‐4 and its anticancer activity in vitro

Abstract: The fermentation product of Cordyceps sinensis mycelium Cs‐4 was commonly used as alternative substitutes of natural C. sinensis. Massoia lactone is the dominant component in the volatile oil of Cs‐4 mycelium. In this research, we present a high performance liquid chromatography (HPLC) method for the quantitation of massoia lactone in Cs‐4 mycelium. The high and stable contents of massoia lactone with values of 2.98–3.77 mg/g, indicated that massoia lactone could be considered as a marker for the quality asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…[5][6][7][8] Massoia lactone released from liamocins has anticancer activity and antifungal activity. [9][10][11][12][13] Therefore, Massoia lactone released from Peng Wang and Mei Zhang made equal contribution to this study. liamocins also has many applications in pharmaceutical and agricultural industries, [5][6][7][8] For example, Massoia lactone has high anti-fungal activity against the pathogenic yeast in aquacultural animals and the pathogenic fungi in crops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Massoia lactone released from liamocins has anticancer activity and antifungal activity. [9][10][11][12][13] Therefore, Massoia lactone released from Peng Wang and Mei Zhang made equal contribution to this study. liamocins also has many applications in pharmaceutical and agricultural industries, [5][6][7][8] For example, Massoia lactone has high anti-fungal activity against the pathogenic yeast in aquacultural animals and the pathogenic fungi in crops.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5–8 ] Massoia lactone released from liamocins has anticancer activity and antifungal activity. [ 9–13 ] Therefore, Massoia lactone released from liamocins also has many applications in pharmaceutical and agricultural industries, [ 5–8 ] For example, Massoia lactone has high anti‐fungal activity against the pathogenic yeast in aquacultural animals and the pathogenic fungi in crops. [ 1,12,14 ] Meanwhile, Massoia lactone released from liamocins as a high‐value product also can be used in flavor and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al [ 28 ] developed massoia lactone-loaded and food-grade nanoemulsions and evaluated their antifungal activity against Metschnikowia bicuspidate , a pathogenic yeast that causes milky disease in the Chinese mitten crab. Furthermore, apart from demonstrating antifungal activities against pathogenic yeasts, both MEO and C10 also possess anticancer and anti-inflammatory effects [ 29 , 30 ]. Recently, Zhang et al [ 31 ] demonstrated the inhibitory effect of C10 on the growth of 21 crop pathogens, including A. flavus .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 43.04 ± 1.2 g L −1 of extracellular liamocins can be produced and secreted by a marine-derived yeast-like fungus Aureobasidium melanogenum M39 expressing homologous PYC1 gene encoding pyruvate carboxylase and alkaline hydrolysis of the extracellular liamocins can release 39.6 g L −1 of 5-hydroxy-2-decenoic acid lactone into medium [5]. Much research work has demonstrated that C-10 Massoia lactone has antifungal, antiviral, anticancer, and anti-inflammatory activities, suggesting that it could be applied to many sectors of agricultural, industrial, pharmaceutical and food industries [1,[6][7][8][9]. For example, the treatment of the pathogenic yeast strain LIAO causing the milky disease in the Chinese mitten, an important food in China and other countries with Massoia lactone can damage its cell membrane, even break its whole cells and cause its cellular necrosis [4].…”
Section: Introductionmentioning
confidence: 99%